EDUCATING THE IMPACT OF COCONUT SPROUT ON MATERNAL HYPERTENSION IN TANGERANG, INDONESIA: A CASE STUDY - Aiba, Sumiaty; Larosa, Desman Berkati; Yoche, Maria Maxmila; Rumerung, Christie Lidia; Sitomorang, Komilie (Journal of Public Health Research and Community Health Development, 2023)
ABSTRACT Background: The effects of hypertension during pregnancy have caused health problems serious to mother and fetus. Hypertension can affect fetal development, and sudden fetal and maternal death. One source of plant nutrients that can optimize the number of blood cells is coconut sprout. Purpose: Coconut sprouts are high in carbohydrates, fiber, and antioxidants that can help optimize maternal health during pregnancy and reduce the risk of hypertension during pregnancy, however, not many women are aware of this information. Methods: This study attempts to inform pregnant women of the benefit of coconut sprout using lectures and demonstration along with primary health centre activities.  A pretest and a posttest were conducted to assess improvement in knowledge. The total number of participants who participated in the activities was 50 people. The age range of pregnant women was 23-38 years old. Result: Knowledge of participants before the presentation of the material were low, with an average score of 35.41%, compared to 64.55% after the explanation. The comparison of participants' knowledge before and after education was 29.14%. The educational activities and dissemination conducted in the Binong Public Health Center area was to add, expand, and improve participants' knowledge of the impact of hypertension during pregnancy. Conclusion: Activities that needed to be continued was checking up urine, protein during pregnancy, direct application of coconut sprouts with controlling laboratory results, and increasing socialization, health promotion about the impact of hypertension, and the use of coconut sprouts to the general public.